Hybrid Blood Purification Therapy Based on Camel Nanoantibody Immunoadsorbent on Patients with Chronic Renal Failure in Nephrology Department - Tao Ma; Li Wang; Xiuyong Li (Journal of Chemistry)
This paper proposes a study on the effect of hybrid blood purification therapy based on camel nanoantibody immunoadsorbent on chronic renal failure patients in nephrology department. In this paper, the hybrid blood purification therapy based on camel nanoantibody immunoadsorbent was applied to patients with chronic renal failure, and the curative effect of the patients was studied. In order to highlight the effect, a control group was set up for comparison. In this paper, the clearance effect of small molecule toxin, middle molecular toxin, and dialysis adequacy was analyzed. This study found that the average dialysis adequacy of the control group was 1.23% and that of the experimental group was 1.26%. The dialysis adequacy of the experimental group was significantly better than that of the control group. In addition, the clearance effect of small and medium molecular toxins in the experimental group was significantly better than that in the control group. It can be seen that the hybrid blood purification therapy based on camel nanoantibody immunoadsorbent is effective in the treatment of chronic renal failure patients in the department of nephrology. Therefore, it is of great value to apply camel nanoantibody in the clinical treatment of renal failure.